Influence of obesity and other metabolic disorders on rosacea - Kamila Fularska; Aleksandra Kuźniar; Dominik Szawica; Edward Wąsiewicz; Michał Oleszko; Fryderyk Sobczak; Radosław Bernacki; Piotr Bernacki; Martyna Dutka; Witold Zardzewiały (Kazimierz Wielki University, 2023)
Introduction:Rosacea is a chronic, inflammatory disease, characterized by skin lesions or ocular symptoms. Skin lesions are located primarily on the central face. Thickening of the skin can occur in some people. There are four subtypes of rosacea and one variant. Rosacea significantly impairs the quality of life. The exact cause of rosacea is not yet fully understood, but it is thought to involve a combination of genetic, environmental, and lifestyle factors. Treatment starts with avoidance of triggering factors. Obesity leads to multiple negative health effects. It has been associated with some inflammatory dermatoses, such as psoriasis and atopic dermatitis.As obesity disrupt cutaneous vasculature and temperature regulation, it may be also associated with increased risk for rosacea and worse course of this disease.  Aim of study:The purpose of the study was to review the literature on the influence of  obesity and other metabolic disorders on development of rosacea. Matherials and methods:A systemic review was conducted using PubMed, ScienceDirect, Google Scholar databases. The search strategy was based on following terms: rosacea, BMI, obesity, overweight, metabolic changes, insulin resistance and rosacea Results and Conclusions:The complex relationship between obesity and other metabolic disorders and rosacea goes beyond obvious binary relationships. Chronic inflammation, genetic predisposition, common risk factors, and changes in metabolic and vascular function contribute to their complex interaction.Recognition and understanding of this relationship offers the potential for the development of new treatment strategies in the future that will prevent the occurrence of rosacea by modifying i.a. the risk factors we describe before they affect the patient's health and cause the disease described. Future research should continue to explore the underlying mechanisms and therapeutic interventions